2021
DOI: 10.31763/ijrcs.v1i3.363
|View full text |Cite
|
Sign up to set email alerts
|

Review of Aerial Manipulator and its Control

Abstract: The aerial manipulator is a new type of aerial robot with active operation capability, which is composed of a rotary-wing drone and an actuator. Although aerial manipulation has greatly increased the scope of robot operations, the research on aerial manipulators also faces many difficulties, such as the selection of aerial platforms and actuators, system modeling and control, etc. This article attempts to collect the research team’s Achievements in the field of aerial robotic arms. The main results of the aeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…So our solution is not only easy to use, but compared to other solutions, it also has low network and hardware requirements. Moreover, another advantage of our approach is its modularity and it can be modified and enhanced in different ways (e.g., methods other than standard A* can be used for local planning [39][41] [42] or the solution can be extended to 3D for the usage of drones in industrial environment [40]).…”
Section: Resultsmentioning
confidence: 99%
“…So our solution is not only easy to use, but compared to other solutions, it also has low network and hardware requirements. Moreover, another advantage of our approach is its modularity and it can be modified and enhanced in different ways (e.g., methods other than standard A* can be used for local planning [39][41] [42] or the solution can be extended to 3D for the usage of drones in industrial environment [40]).…”
Section: Resultsmentioning
confidence: 99%
“…Quadcopters, hexacopters, helicopters, coaxial octorotors, ducted fan UAVs, tilt hexarotors, and other vehicles have been used as flying robots' floating bases. A thorough review of the literature on aerial robots can be found in Delmerico et al (2019), Khamseh et al (2018), Meng et al (2020), Mohiuddin et al (2020), Ruggiero et al (2018), Wei‐hong et al (2021), Xilun et al (2019) and in Suarez et al (2022), where a collection of research work on different aspects of aerial robots used in inspection and maintenance operations is presented. Quadcopters, one of the most extensively used UAVs, offer various applications in industry and research.…”
Section: Introductionmentioning
confidence: 99%